The influence of substance misuse on clinical outcomes following burn() - Rehou, Sarah (Burns, 2017)
INTRODUCTION: Ongoing increases in the prevalence of substance misuse among burn-injured patients necessitate a contemporary analysis of the association between substance misuse and clinical outcomes in burn-injured adults. METHODS: We conducted a retrospective cohort study of 1199 patients admitted to a regional burn center. History of substance misuse was derived from a prospective clinical registry and categorized as alcohol, illicit drug, or both. The primary outcome was hospital length of stay; association of substance misuse and inpatient complications were secondary outcomes. Multivariable logistic regression was used to model the association between categories of substance misuse and each outcome, adjusting for patient and injury characteristics. RESULTS: The incidence of substance misuse was 34% overall. After adjustment for patient and injury characteristics, drug misuse was associated with a significantly longer length of stay (RR 1.12; 95% CI 1.00–1.25), as was alcohol misuse (RR 1.32; 95% CI 1.14–1.52), and drug/alcohol misuse (RR 1.34; 95% CI 1.16–1.56). Drug/alcohol misuse was associated with significantly higher rates of bacteremia (OR 3.84; 95% CI 1.83–8.04) and sepsis (OR 2.50; CI1.13–5.53). CONCLUSIONS: A history of substance misuse is associated with an increased risk of inpatient complications and longer hospital stay. Providers should be cognizant of increased complications in this cohort with a view to improving outcomes.